PCB-waste derived resin as a binary ion exchanger for zinc removal: Isotherm modelling and adsorbent optimization - Shifa Zuhara (14150862) (2023)
Effective removal of heavy metals from wastewaters can enable increased reuse of treated wastewater and reduce water scarcity worldwide. This paper describes the results of an initial study on zinc removal using waste-derived aluminosilicate-based material by binary ion exchange with calcium and potassium. About 2 mmol/g of zinc removal adsorption capacity was demonstrated using the aluminosilicate resin. Seven equilibrium isotherm models have been analyzed using the zinc adsorption data; the best fit to the experimental values based on the lowest SSE error was the SIPS model. A mechanism between zinc adsorption and the calcium and potassium desorption has been developed and modelled and is confirmed based on the mass balance analysis between the divalent calcium ions and the monovalent potassium ions exchanged with the divalent zinc ions adsorbed. Desorption studies using isotherm model equations for the calcium and potassium data further confirmed the mechanism. Regeneration was over 80% per cycle for three acid regenerations, indicating the zinc can be recovered for re-use. Furthermore, optimization using the SIPS model showed the minimum amount of adsorbent required using a two-stage reactor system is much lower, proving the need for a two-stage reactor to make the system more economical. Future experiments on multicomponent analysis and further optimization will help develop this adsorbent for real water systems. Other Information Published in: Chemical Papers License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11696-023-02823-2